Reducing the nucleation barrier in magnetocaloric Heusler alloys by nanoindentation - Niemann, R.; Hahn, S.; Diestel, A.; Backen, A.; Schultz, Ludwig; Nielsch, Kornelius; Wagner, M. F. -X.; Faehler, S. (APL Materials, 2016)
Magnetocaloric materials are promising as solid state refrigerants for more efficient and environmentally friendly cooling devices. The highest effects have been observed in materials that exhibit a first-order phase transition. These transformations proceed by nucleation and growth which lead to a hysteresis. Such irreversible processes are undesired since they heat up the material and reduce the efficiency of any cooling application. In this article, we demonstrate an approach to decrease the hysteresis by locally changing the nucleation barrier. We created artificial nucleation sites and analyzed the nucleation and growth processes in their proximity. We use Ni-Mn-Ga, a shape memory alloy that exhibits a martensitic transformation. Epitaxial films serve as a model system, but their high surface-to-volume ratio also allows for a fast heat transfer which is beneficial for a magnetocaloric regenerator geometry. Nanoindentation is used to create a well-defined defect. We quantify the austenite phase fraction in its proximity as a function of temperature which allows us to determine the influence of the defect on the transformation.
CRIS-Team Scopus Importer:2023-03-20